Biopesticide Potential of Laurus nobilis and Inula viscosa Essential Oils for the Management of Tomato Leaf Miner (Tuta absoluta) - Tchouar, Siham; Gaouar Benyelles, Nassira; Tabti, Leila; Morsli, El Mehdi (Department of Agronomy and Horticulture, IPB University, 2026)
The tomato leaf miner, Tuta absoluta, is one of the most destructive tomato pests worldwide. The use of chemical pesticides can improve yield and fruit quality; however, it poses serious risks to human health and the environment. Consequently, research efforts are increasingly focusing on sustainable, eco-friendly pest management strategies, including the use of essential oils as biopesticides. This study evaluates the insecticidal activity of Laurus nobilis and Inula viscosa essential oils against the four larval instars of T. absoluta. Essential oils were assessed using a contact toxicity assay, with each dose tested across all larval instars and compared with an untreated control. Lethal doses (LD50 and LD90) were estimated using Probit regression analysis. The bioassays showed that both essential oils exhibited significant larvicidal activity with dose- and stage-dependent mortality. Early larval instars required lower doses to achieve 50% and 90% mortality (10, 20, and 30 µl for I. viscosa; 3, 5, and 10 µl for L. nobilis), whereas later instars were more tolerant and required higher doses. Complete mortality of all four larval instars was obtained at 100 µl of I. viscosa and 30 µl of L. nobilis. Overall, these findings demonstrate the larvicidal potential of these essential oils and support their use as biopesticides within integrated pest management programs in agriculture. To our knowledge, this is the first report of the larvicidal activity of the essential oils from I. viscosa and L. nobilis against T. absoluta in Algeria.